A comparative Assessment of Aspergillus niger and Fusarium pallidoroseum for Synthesizing Metal‐Nanoparticles of Zinc and Silver. Issue 1 (23rd February 2023) - Shukla, Gyanika; Singh, Amardeep; Gaurav, Shailendra Singh; Rani, Poonam
Abstract: The present study is carried to establish and compare the mycogenic silver nanoparticles (AgNPs) and zinc oxide nanoparticles (ZnONPs) synthesizing ability of two fungi, Aspergillus niger and Fusarium pallidoroseum . A 2 mM solution of silver nitrate and zinc nitrate hexahydrate is used as the precursor solution for the synthesis of silver and zinc oxide nanoparticles respectively using 1 g and 100 mg fungal biomass per 100 mL of the precursor solution. The synthesis of nanoparticles is preliminarily confirmed by UV–Vis Spectroscopy and further characterization is done through the Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X‐Ray (EDX), Dynamic Light Scattering (DLS), Fourier Transform Infra‐Red (FTIR), and Inductively Coupled Plasma Mass Spectrometry (ICPMS) to characterize the nanoparticles in terms of shape, size, and concentration. The particles synthesized by using 100 mg fungal biomass are much agglomerated and bulky in size. The study concludes that 1 g F. pallidoroseum biomass showed much efficacy toward synthesizing fine‐sized ZnONPs as compared to A. niger, whereas, although the AgNPs synthesized by A. niger are more monodispersed with least agglomeration, the efficacy of A. niger and F. pallidoroseum is found to be mostly comparable in synthesizing AgNPs.